2006
DOI: 10.1111/j.1365-2672.2006.03005.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of naphthenic acids by sediment micro-organisms

Abstract: Aims:  Naphthenic acids (NAs) are naturally occurring, linear and cyclic carboxylic surfactants associated with the acidic fraction of petroleum. NAs account for most of the acute aquatic toxicity of oil sands process‐affected water (OSPW). The toxicity of OSPW can be reduced by microbial degradation. The aim of this research was to determine the extent of NA degradation by sediment microbial communities exposed to varying amounts of OSPW. Methods and Results:  Eleven wetlands, both natural and process‐affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(64 citation statements)
references
References 28 publications
3
61
0
Order By: Relevance
“…Using the GC-MS technique to characterize the NAs, Scott et al (2005) showed that commercial NAs, with a greater proportion of lower molecular weight NAs with shorter carbon chains and fewer rings, were more easily degraded than the oil sands derived NAs. Other studies have also documented differences in the makeup of NA (Herman et al 1993;Herman et al 1994;Lai et al 1996;Clemente et al 2004;Del Rio et al 2006). It is possible that only a limited fraction of the NAs within the oil sands derived mixture is readily degraded, whereas the commercial mix may be more broadly metabolized.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Using the GC-MS technique to characterize the NAs, Scott et al (2005) showed that commercial NAs, with a greater proportion of lower molecular weight NAs with shorter carbon chains and fewer rings, were more easily degraded than the oil sands derived NAs. Other studies have also documented differences in the makeup of NA (Herman et al 1993;Herman et al 1994;Lai et al 1996;Clemente et al 2004;Del Rio et al 2006). It is possible that only a limited fraction of the NAs within the oil sands derived mixture is readily degraded, whereas the commercial mix may be more broadly metabolized.…”
Section: Discussionmentioning
confidence: 95%
“…Hall et al (1999) found differences in the δ 13 C values of CO 2 depending on the chemical degraded (phenol vs. benzoate) and the species of microorganism used, but found no change in the δ 13 C values of microbial biomass. While there is information on the rate of biodegradation of various surrogate NAs (Herman et al 1993;Lai et al 1996;Del Rio et al 2006) as well as commercial and oil sands processderived NA mixtures (Herman et al 1994;Clemente et al 2004;Scott et al 2005;Del Rio et al 2006), there has been no tracking of stable isotopes during microbial degradation of NAs.…”
Section: Introductionmentioning
confidence: 98%
“…The wastewater generated is known as oil sands process-affected water (OSPW). OSPW has demonstrated both acute and chronic toxicity to a number of species (Del Rio et al 2006;Wang et al 2013). The toxicity of OSPW is mainly due to the presence of a group of dissolved organic acids, known as Bnaphthenic acids^(NAs) which refer to a complex suite of alkyl-substituted acyclic and cycloaliphatic carboxylic acids (Clemente et al 2004;Ahad et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Though technology is advancing rapidly to store produced water as shallow groundwater in clay and gypsum slurries, thickened tails, and polymer enriched sludges, tailings pond reclamation is an unproven technology. Companies do not yet have a cost-effective way to remediate the volumes of water produced and they may have to store it for decades to centuries (Del Rio et al 2006).…”
Section: Watermentioning
confidence: 99%